Branded Content: Nuevas formas de Comunicación de marca en el GADM de Riobamba, de mayo del 2023 a mayo del 2024 - Guamán Naula, Ingrid Nathaly (2025)
This paper analyzes new forms of brand communication through branded content implemented by the Municipal Decentralized Autonomous Government (GADM) of Riobamba from May 2023 to May 2024. In response to increasing digitalization and the need to strengthen institutional identity, the study examines the impact of these strategies on public perception, identifies areas for improvement, and proposes a theoretical framework to optimize communication management in the public sector. The main objectives were to establish the principles of branded content, storytelling, and digital segmentation applicable to the GADM; to structure a hero, hub, and help content strategy adapted to digital platforms; and to propose a communication performance evaluation framework. The methodology applied was qualitative, with a sequential exploration design, utilizing techniques such as social media content analysis and semi-structured interviews with experts and officials. The results show that the branded content strategies employed by the GADM of Riobamba had a moderate impact on public perception, with greater effectiveness observed in audiovisual formats and platforms such as TikTok and Instagram. However, weaknesses were identified in narrative construction, emotional integration, and the systematic measurement of outcomes. As a conclusion, the study confirms the need to structure communication around symbolic storytelling that fosters identity and a sense of belonging. In response, a theoretical proposal was developed, presenting a strategic branded content plan with clear guidelines to strengthen the institutional brand through emotionally resonant, segmented, and measurable narrative content.